Semantic Shifts in Fantastic Beasts and Where to Find Them: The Original Screenplay Novel - Melida, Melida; Zami, Hella Novita; Tika, Herni (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
The differences in language systems cause a translator to have difficulty in searching for equivalent words. The difficulty that the translator has in obtaining equivalences is exacerbated when the word class changes during translation. If it happens large enough, it may change the lexical relations between two words. Lexical relations can be big problems for the translators if they do not understand them and look into them well enough. This research aimed to identify the types of class shifts and lexical relations in the texts of Fantastic Beasts and Where to Find Them: The Original Screenplay Novel. This research used a qualitative method to analyze the novel because it analyzed the words of the texts in that novel. Fifteen scenes were chosen by the researcher based on the total engagement. The fifteen scenes located in a subway. The results showed that there were nine types of class shifts that were found in this study. They were noun to verb, pronoun to noun, preposition to verb, adjective to verb, adverb to adjective, adverb to verb, verb to noun, verb to adverb, and adjective to noun. From nine types of class shifts, the types of lexical relation were found are synonymy and hyponymy. Class shifts could happen anytime. The occurrence of class shifts did not vouch for the occurrence of lexical relation. It was affected by the translator himself/ herself.